Prophylactic vaccination against human papillomaviruses to prevent vulval and vaginal cancer and their precursors. (2nd November 2019) - Xu, Lan; Selk, Amanda; Garland, Suzanne M; Bogliatto, Fabrizio; Kyrgiou, Maria; Weyers, Steven; Arbyn, Marc
ABSTRACT: Introduction : Safety and efficacy of prophylactic HPV vaccines against HPV infection and associated cervical cancers and precursors is well documented in the literature; however, their efficacy against vulval and vaginal endpoints has not been previously assessed. Areas covered : Published results of trials involving licensed HPV vaccines were included. Main efficacy outcomes were histologically confirmed high-grade vulval and vaginal precancer distinguishing those associated with vaccine HPV types and any vulval and vaginal precancerous lesions. Exposure groups included women aged 15–26 or 24–45 years being initially negative for high-risk HPV (hrHPV), negative for the HPV vaccine types, and women unselected by HPV status. Expert opinion : Our results show that the HPV vaccines are equally highly efficacious against vulval/vaginal disease as previously noted for cervical disease. The vaccines demonstrated excellent protection against high-grade vulval and vaginal lesions caused by vaccine-related HPV types among young women who were not initially infected with hrHPV types or types included in the vaccines (vaccine efficacies more than 90%). No protection against high-grade vulval and vaginal lesions associated with HPV16/18 was observed for mid-adult women. Trials were not powered to address protection against invasive cancers.